Consumo de sustancias psicotropicas e incidencia en sus relaciones familiares - Mendoza Paredes, Hilda Irene (2021)
This research was carried out through the analysis of the consumption of psychotropic substances in a 21-year-old man and its influence on his family relationship, which is referred by the technician from the Specialized Center for the treatment of problematic alcohol and other drugs "CETAD, which he attended for his will. Consumption of psychotropic substances affects everyone who uses it, given that its impact on their social, work, and family relationships can be observed, presenting poorly adaptive behaviors in the environment in which they develop, which is why this research was obtained under the use of quantitative methodology with techniques such as the interview, clinical history and psychometric tests which helped to obtain reliable information from the person studied in which signs and symptoms that meet the criteria established by the CIE-10: Cocaine Withdrawal Syndrome (F14.3). Other specified problems related to primary support group. For which a psychotherapeutic plan was developed in order to address these problems identified in the course of the sessions, which were Consumption of psychotropic substances, cognitive distortions and family relationships.